Resilience and Adaptation of Islamic Educational Institutions in Minority Contexts: The Case of Pesantren in Nias - Gea, Yusnidar; Arsyad, Junaidi; OK, Azizah Hanum (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research examines the dynamics of Islamic educational institutions in Muslim-minority regions through case studies of Pondok Pesantren Putri Ummi Kalsum and Pondok Pesantren Hidayatullah in Gunungsitoli City. The central issue lies in how pesantren are able to survive and grow amid the dominance of a non-Muslim society. The objective of the study is to reveal strategies of existence, institutional adaptation, and the socio-religious roles of pesantren within the local context. The research employs a qualitative approach with a multi-site case study design, using data collection techniques such as interviews, observation, and documentation. Data were analyzed using Miles and Huberman’s interactive model. The findings show that both pesantren have successfully become centers of education, dakwah, and the strengthening of Islamic identity through adaptive strategies, local leadership, and constructive social integration.